Hazardous chemicals handbook - Carson, P. A. (Phillip A.), 1944- (Butterworth-Heinemann, 1994)
Provides the core information about the properties of chemicals, exposure limits, flashpoints, monitoring techniques, personal protection, and other parameters and requirements for protecting people and the environment. Summarizes core information for quick reference in the workplace or in transit. Provides ready-reference to help in the often complex task of handling, using, and disposing of chemicals safely.